Utilizing bioinformatics and machine learning to identify CXCR4 gene-related therapeutic targets in diabetic foot ulcers - Zhang, Hengyan; Zhou, Ye; Yan, Heguo; Huang, Changxing; Yang, Licong; Liu, Yangwen (Frontiers in Endocrinology, 2025)
BackgroundDiabetic foot ulcers (DFUs) are a serious complication of diabetes mellitus that manifests as chronic, non-healing wounds that have a significant impact on patients quality of life. Identifying key molecular targets associated with DFUs could help develop targeted therapies to promote wound healing and prevent further complications. The CXCR4 gene is known to play a key role in cell migration, immunology response, and tissue repair, and thus may be an important target for DFU treatment.MethodsWe used the GEO database (Gene Expression Omnibus database) to obtain DFU-related gene expression data, identified differentially expressed genes (DEGs), and performed enrichment analysis to reveal the related biological pathways. Meanwhile, protein-protein interaction (PPI) networks were constructed using STRING to identify core genes. Feature selection methods such as LASSO, SVM-RFE and random forest algorithm were applied to localize possible therapeutic target genes. Finally, We analyzed the molecular pathways of CXCR4 in DFUs by Gene set enrichment analysis (GSEA).ResultsWe identified a total of 751 differential genes, of which 409 genes were significantly upregulated and 342 genes were downregulated in diabetic foot ulcer tissues. Functional enrichment analysis showed that these genes were mainly involved in pathways such as oxidative phosphorylation, phagosome, synaptic vesicle cycle, and pathways of neurodegeneration. We integrated the genes screened by three machine learning models (LASSO, SVM, and Random Forest), and CXCR4 was identified as a key gene with potential therapeutic value in DFUs. Gene set enrichment analysis (GSEA) showed that CXCR4 was closely associated with pathways related to immunology regulation and tissue repair.ConclusionThe findings suggest that CXCR4 and its related pathways play an important role in the pathogenesis of DFUs, providing a new perspective on targeted therapy for wound healing in diabetic patients. Further validation of the role of CXCR4 is expected to establish it as an important target in DFU management.